A God who does not grant salvation to the sinner? - Sanz Giménez-Rico, SJ, Enrique (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
The suffering of the psalmist and his distressed complaint echo repeatedly in the first two Psalms of the unit 79-82. God’s action, which remains unclear and mysterious, seems to confuse his prayer of urging Elohim to «Let your face shine [on us], save us and make us anew.» The theme of salvation that comes across in Psalm 79-80, openly evokes the main salvific event of the Isralites which is narrated in the book of Exodus, namely, the gift of life and freedom which God grants to God’s people. An invocation, which gradually disappears in Psalm 81-82, takes a prominent and central place referring particularly to the Decalogue in Psalm 81. Such an invocation highlights this important succession: «Psalmist’s petition-God’s petition». A careful study of the four indicated Psalms and, particularly of the two elements outlined so far, namely, salvation and succession, opens the door towards considering one aspect of God. Interestingly, such an aspect seems to be present in Psalm 79-82 and does not appear in other Old Testament texts. All suggest that prior to placing a ban on disclosing his salvific nature, God has set conditions to deliver God’s salvation.
Keywords: Psalms 79-82; petition to God and God’s petition; idolatry; name